Myeloid-derived suppressor cells interact with tumors in terms of myelopoiesis, tumorigenesis and immunosuppression: thick as thieves - Sevko, Alexandra; Umansky, Viktor (Journal of cancer, 2013)
Tumor progression is often associated with chronic inflammation in the tumor microenvironment, which is mediated by numerous cytokines, chemokines and growth factors produced by cancer and stroma cells. All these mediators support tumor development and immunosuppression in autocrine and/or paracrine ways. Neutralization of chronic inflammatory conditions can lead to the restoration of anti-tumor immune responses. Among stroma cells infiltrating tumors, myeloid-derived suppressor cells (MDSCs) represent one of the most important players mediating immunosuppression. These cells may not only inhibit an anti-tumor immunity but also directly stimulate tumorigenesis as well as tumor growth and expansion. Therefore, understanding the mechanisms of generation, migration to the tumor site and activation of MDSC is necessary for the development of new strategies of tumor immunotherapy.